2000
DOI: 10.1080/00288330.2000.9516913
|View full text |Cite
|
Sign up to set email alerts
|

Three recently recordedOstreopsisspp. (Dinophyceae) in New Zealand: Temporal and regional distribution in the upper North Island from 1995 to 1997

Abstract: Three species of epiphytic dinoflagellates-Ostreopsis siamensis, O. lenticularis, and O. ovata have recently been found on both the east and west coasts of the upper North Island, New Zealand. The morphological differences of all three Received 29 August 1998; accepted 27 September 1999 Ostreopsis spp. have been studied with both light and scanning electron microscopes. Detailed studies of the inner face of the thecal wall of Ostreopsis siamensis revealed two types of trichocyst pores: small, simple pores a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0
5

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 9 publications
4
52
0
5
Order By: Relevance
“…siamensis strains given by Penna et al (2005) and Aligizaki & Nikolaidis (2006), an affinity confirmed by the molecular analysis. The morphology of the local strains of Ostreopsis also fits the description given by Fukuyo (1981) for O. siamensis, except in cell size (smaller in our strains), and differs from that given by Faust et al (1996) and Chang et al (2000) in having only one size of thecal pores.…”
Section: Taxonomic Remarksmentioning
confidence: 48%
“…siamensis strains given by Penna et al (2005) and Aligizaki & Nikolaidis (2006), an affinity confirmed by the molecular analysis. The morphology of the local strains of Ostreopsis also fits the description given by Fukuyo (1981) for O. siamensis, except in cell size (smaller in our strains), and differs from that given by Faust et al (1996) and Chang et al (2000) in having only one size of thecal pores.…”
Section: Taxonomic Remarksmentioning
confidence: 48%
“…Other less abundant species included P. lima, P. compressum and C. monotis. There was also clear regional difference in their distribution and cell concentrations of the dominant species (Chang et al, 2000).…”
Section: Bloom-forming Cfp-dinoflagellatesmentioning
confidence: 98%
“…Ostreopsis spp. is common epiphytic species in northern New Zealand (Rhodes et al, 2000 (Chang et al, 2000). Dinoflagellate culture isolates of Ostreopsis exhibited rapid growth rates after reaching 31 o C (Tindall and Morton, 1998).…”
Section: Floating Detritus-specialized Environment Of Harmful and Cfpmentioning
confidence: 99%
“…However, the link between toxins and the presence of Ostreopsis siamensis is not yet clear (Chang et al 2000). The epiphytic community toxicity in Catalonia had been tested by injecting the extract (intraperitoneally) into mice (modified from the Association of Official Analytic Chemists 1980, Yasumoto et al 1980).…”
Section: The Epiphytic Dinoflagellate Assemblage In the Mediterraneanmentioning
confidence: 99%
“…The dominant species, O. siamensis, accounted for 64 to 85% of the total epiphytic flora during summer (Chang et al 2000). Although Gambierdiscus toxicus and O. lenticularis are co-dominant in many tropical regions (Bagins et al 1985, Ballantine et al 1985, Carlson & Tindall 1985, Gillespie et al 1985, Bomber & Aikman 1989, G. toxicus has been recorded only once (and in extremely low concentrations) in northern New Zealand (Chang et al 2000) and never on the Catalan coast. There may be a latitudinal gradient that implies different species composition within the benthic association.…”
mentioning
confidence: 99%